A Travelling Lamaštu - Ermidoro, Stefania (Altorientalische Forschungen, 2017)
The article presents a study of the text and iconography of the item previously identified by Farber as “Lamaštu-Amulett Nr. 70F”. In 1989, Farber described the amulet and published its textual content by means of some photographs. Recently, however, the present author had the opportunity to inspect the same item in a private collection in Italy. The results of the new collation are provided here, including a description of the specific characteristics and technical features of the object. It is argued here that the amulet is without a doubt a modern copy, which accurately duplicates an ancient piece: at the end of the article, photos provide evidence of all the surfaces of the object.